Concerns About Co-Authoring AI Tools in Academic Papers - Yildiz, Emrah (European Journal of Therapeutics, 2023)
Dear Editors With great attention and interest, I read the editors’ short brief yet thought-provoking editorials [1,2] and it has helped me combine valuable information with my research and experiences. Today, artificial intelligence has become an application that we can use in all areas of our lives, being versatile, and able to analyze, collect and interpret. Writing ChatGPT that we can barely bring together for weeks or even months of work, and other AI applications can be used in minutes or even. We seconds can see that it produces original writings and offers a wide range of information. It is obvious that the time-saving experience provided by artificial intelligence provides convenience in most areas of our lives. But that’s human researchers and artificial intelligence it may cause us to not understand some points about certain differences between the two. For example, when we look at the difference between an article written with artificial intelligence and an article written with human intelligence, it is undoubtedly almost understandable at first glance impossible. Because of life’s developing and changing conditions, no field wanted to be left behind and turned to itself to build its essence, one of which is undoubtedly artificial Intelligence. With the rapid progression of the COVID-19 pandemic and swiftly evolving political decisions, technology has become exceedingly practical and adaptive, undergoing continuous transformation. Many research studies have begun to be conducted around the world, with the need for individuals to conduct faster and more extensive research to bring together new and diverse resources. While the utilization of artificial intelligence (AI) appears as one of the most promising options for this purpose, we must inquire whether its inclusion as a co-author adheres to ethical and technical standards or if it occasionally neglects these principles. In my opinion, involving AI tools like ChatGPT as a co-author can potentially lead to ethical complexities, especially in terms of responsibility and accountability. Language models powered by artificial intelligence lack consciousness, autonomy, and the ability to claim ownership of their contributions. Ascribing authorship to these models blurs lines of responsibility and weakens the ethical obligations inherent in scholarly authorship. Simultaneously, the essence of scholarly authorship lies in the generation of hypotheses, experimentation, data analysis, and interpretation, attributes ascribed to individuals who actively contribute. In this context, even though ChatGPT and other artificial intelligence models expeditiously furnish us with desired information through rapid interactions, it is fundamentally derived from existing human input sources. In essence, these AI systems do not so much transform or recreate a wellspring of knowledge as they present it in its preexisting state. Introducing ChatGPT as a co-author could evoke the assumption of its active engagement, potentially blurring the distinction between the assistance offered by researchers and that by the AI, rendering it challenging for observers to distinctly discern their respective contributions. Consequently, artificial intelligence’s contributions, evident when examining scientific articles and many other sources we seek, are undeniably substantial. While the knowledge it presents may introduce entirely novel perspectives, rather than accrediting artificial intelligence as an author, we should confine its recognition to the acknowledgment section solely for its contributions. This approach allows us to acknowledge the collaborative efforts of both human and artificial intelligence, upholding transparency while respecting and adhering to traditional authorship norms. Yours sincerely,